Pengaruh Earning Per Share Terhadap Harga Saham Pada PT Panin Sekuritas Tbk. Yang Terdaftar Di Bursa Efek Indonesia Periode (2006 – 2017) - Indri Ayu Tansar; Tri Ningsih; Resi Fujianti (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2018)
This research wants to determine the influence of earning per share (EPS) caused of stock prices at PT Panin Sekuritas Tbk., which listed on Indonesia Stock Exchange. The research sample used data the development of earning per share and stock prices PT Panin Sekuritas Tbk. A method of the research uses simple linier regression test. The research results show that the coefficients determination obtained correlation value (R) from of 0,593 or 59.3 % which showed that dependent variable and independent variable having positive strong correlation, while value the coefficients determination R adjused r2 out of 0,352 or 35.2 %. However statistical tests and the results of SPSS showed that from variable x (EPS) have tcount 0,777. This value is smaller than ttable 2.616. This showed variable EPS statistically have significant impact on the price of shares in PT Panin Sekuritas Tbk.